Penanaman Konsep Hayā' sebagai Landasan Pendidikan Seksual Anak Usia Dini - Fitrah Nabila Dista; Wirda Rahmita (Institut Agama Islam Negeri Madura, 2024)
This study aims to examine the effectiveness of instilling the Hayā' concept as a basis for sexual education in early childhood. Using a qualitative approach with a case study method, the study was conducted at Dharma Wanita Teunom State Kindergarten with subjects of 10 children in class B1 (aged 5-6 years), 2 class teachers, and 10 parents, through participatory observation, in-depth interviews, documentation, and Focus Group Discussion (FGD). The results of the study showed a significant increase in the understanding and application of the Hayā' concept in children after the implementation of the program for seven days, especially in three aspects: understanding the ethics of entering the parent's room, awareness of times that require permission, and understanding the boundaries of genitals and attributes according to gender, with the success of the program supported by the use of varied learning methods and synergy between schools and families.